Conquering Pedaphobia: A Case Study of Counselling Interventions - Aina Razlin, Mohammad Roose (Faculty of Cognitive Sciences & Human Development UNIMAS, 2015)
This paper presents a case study of a 22-year-old female client who came for counselling sessions for the purpose of overcoming her pedaphobia. Symptoms, such as, dizziness, nausea, arousal, sweating palm and body shaking were noticed to be visible not only by the presence of a real child, but also by pictures, stories and imaginations of infants. Systematic desensitization technique, a form of Exposure Therapy, was applied to treat the client. It involved relaxation and breathing techniques, and supported by the application of live modelling guided participation. Along with the interventions, Rational Emotive Behaviour Therapy techniques were also applied, such as, thought recording, irrational thoughts identification and disputation, Rational Emotive Imagery (REI), coping self-statement, and forceful self-statement. By the end of the therapy, the client reported to have experienced a decline in the occurrences of symptoms and demonstrated the ability to overcome her phobia.